Prognostic value of galectin-3 and right ventricular function for long-term mortality in heart failure patients treated with cardiac resynchronization therapy - Beata Zaborska (Nature Portfolio, 2021)
Abstract Recently, associations between the biomarker galectin-3 and numerous pathological processes involved in heart failure (HF) and right ventricular (RV) function have been observed. We aimed to assess the long-term prognostic ability of galectin-3 and RV function parameters for all-cause mortality in HF patients treated with cardiac resynchronization therapy (CRT). We prospectively studied 63 symptomatic HF patients with a left ventricular (LV) ejection fraction (EF) ≤ 35%. The median serum galectin-3 concentration was 13.4 ng/mL (IQR 11.05, 17.15). A detailed assessment of LV and RV geometry and function was performed with echocardiography. CRT defibrillator implantation was achieved in all patients without major complications. The follow-up lasted 5 years. In the multivariable Cox regression model, independent predictors for all-cause mortality were log baseline galectin-3 and baseline RV function expressed as tricuspid annular plane systolic excursion with HR 2.96 (p = 0.037) and HR 0.88 (p = 0.023), respectively. Analysis of subgroups defined by galectin-3 concentration and CRT response showed that patients with high baseline galectin-3 concentrations and a lack of response to CRT had a significantly lower probability of survival. In our patient cohort, the baseline galectin-3 concentration and RV function were independent predictors of long-term all-cause mortality in HFrEF patients following CRT implantation.